Clinical characteristics and outcomes of children with COVID-19 in pediatric intensive care units during the Omicron wave in Taiwan - Jeng-Hung Wu; Ching-Chia Wang; Frank Leigh Lu; Shu-Chien Huang; Ting-Yu Yen; Chun-Yi Lu; Luan-Yin Chang; En-Ting Wu (Journal of the Formosan Medical Association)
Background: Since April 2022, the SARS-CoV-2 Omicron variant has caused a notable increase in pediatric COVID-19 cases in Taiwan. During the acute phase of infection, some children required admissions to pediatric intensive care units (PICU). This study aimed to analyze their clinical presentations and outcomes while exploring associated factors. Methods: Medical records were retrospectively collected from patients with COVID-19 (aged <18 years) admitted to our PICU from April 2022–March 2023. Early stage is defined as the period without adequate vaccination and treatment guidelines for children from April–June 2022, and the remaining months are referred to as late stage. Clinical characteristics and outcomes were compared between patients in early and late stages. Results: We enrolled 78 children with COVID-19, with a median length of stay (LOS) in PICU of 3 days and a 5% mortality rate. Patients admitted during the early stage had lower vaccination rates (7% vs. 50%), higher pediatric logistic organ dysfunction scores (2 vs. 0.1), and longer LOS in the PICU (6 vs. 2 days) than those admitted during the late stage. Multivariate analysis identified admission during the early stage as a risk factor for prolonged LOS (>7 days) in the PICU (odds ratio: 3.65, p = 0.047). Conclusion: Without available vaccinations and suitable treatment guidelines, children with COVID-19 tended to have more severe illness and prolonged LOS in the PICU. These observations highlight the importance of vaccinations and familiarity of medical providers with adequate management of this newly-emerging infectious disease.